Green CO2 technology for the preparation of aerogel dry powder loaded with beclomethasone dipropionate - Thoa Duong; Clara López-Iglesias; Annalisa Bianchera; Maria Vivero-Lopez; Inés Ardao; Ruggero Bettini; Carmen Alvarez-Lorenzo; Carlos A. García-González (Journal of CO2 Utilization, 2024)
Dry powder inhalers (DPIs) have gained increasing clinical acceptance in the local treatment of lung diseases due to their ability to meet the evolving needs of patients while avoiding environmental concerns. However, some formulations for DPIs still encounter performance limitations in terms of aerodynamic properties and achievement of therapeutic doses. Innovative aerogel powder formulations for DPIs processed using combined supercritical CO2 (scCO2)-based technologies can overcome these limitations, especially in the case of poorly water-soluble drugs. The loading of hydrophobic drugs into aerogels can be optimized through a thorough understanding of the physicochemical properties of the formulation and the scCO2 processing conditions. In this study, drug-loaded alginate aerogel particles were prepared by combining gelation-emulsification techniques and scCO2-based technologies. Beclomethasone dipropionate (BDP), a hydrophobic corticosteroid, was incorporated into the aerogel matrix by scCO2 impregnation. The influence of contact time, initial amount of drug, and use of co-solvents on the efficiency of scCO2 impregnation were studied. The kinetics of the BDP adsorption process was modelled to elucidate the time required for the drug to attain equilibrium concentration under specific operating conditions. Nitrogen adsorption-desorption and helium pycnometry revealed particles with large surface area (>200 m2/g) and porosity (ca. 90%). The resulting aerogels had excellent aerodynamic properties at relevant BDP doses, as confirmed by in vitro lung deposition tests. Ex vivo permeability tests with porcine lung tissues evidenced that BDP released from the inhaled formulation could penetrate the bronchial tissue.